Pelayanan Pada Peminjaman Dan Pencairan Dana Melalui Program Kurnia (Studi Pada Dinas Koperasi Usaha Mikro Dan Tenaga Kerja Kota Kediri) - Nirmala, Laylatul; Prastyawan, Agus (Jurnal Inovasi Administrasi Negara Terapan (Inovant), 2023)
The government as a provider of public services is demanded for its ability to improve service quality, as well as set service standards. Based on the results of initial observations made by researchers in the field, several complaints were found from the public who submitted loan applications to the Kediri City Cooperative Office. So for this reason the purpose of this study is to describe the application of services as well as the inhibiting factors and supporting factors of services in lending and disbursement of funds through the gift program at the Kediri City Cooperative Service. This study uses a qualitative method. Service measurement refers to Law no. 25 of 2009 article 4. The results of the study show that the Kurnia program can be said to have only 7 principles that have been implemented properly by officers, the remaining 5 principles have not been implemented properly by officers, namely the principle of professionalism, the principle of discriminatory, the principle of openness, the principle of facilities for vulnerable and disabled groups and timeliness principle. The inhibiting factor for services in the Kurnia program is the lack of awareness of officers in providing services in accordance with the SOP so that tasks cannot be completed on time. skills of officers in providing services and adequate facilities and infrastructure.  Keywords: Service, Kurnia Program, UMTK Cooperative Service